Reusable composite membranes for highly efficient chromium removal from real water matrixes. (November 2022) - Queirós, J.M.; Salazar, H.; Valverde, A.; Botelho, G.; Fernández de Luis, R.; Teixeira, J.; Martins, P.M.; Lanceros-Mendez, S.
Abstract: Natural or industrial hexavalent chromium water pollution continues to be a worldwide unresolved threat. Today, there is intense research on new active and cost-effective sorbents for Cr(VI), but most still exhibit a critical limitation: their powdered nature makes their recovery from water cost and energy consuming. In this work, Al(OH)3, MIL-88-B(Fe), and UiO-66-NH2 Cr(VI) sorbents were immobilized into a poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) polymeric substrate to develop an easily reactivable and reusable water filtering technology. The immobilization of the sorbents into the PVDF-HFP porous matrix modified the macro and meso-porous structure of the polymeric matrix, tuning in parallel its wettability. Although a partial blocking of the Cr(VI) adsorptive capacity was observed for of Al(OH)3 and MIL-88-B(Fe) when immobilized into composite membranes, PVDF-HFP/UiO-66-NH2 filter (i) exceeded the full capacity of the non-immobilized sorbent to trap Cr(VI), (ii) could be reactivated and reusable, and (iii) it was fully functional when applied in real water effluents. Graphical abstract: Image 1 Highlights: The removal of Cr VI  through adsorption requires time and cost intensive sorbent's recovery and reactivation. Sorbent nanoparticles immobilization into polymeric membranes offers a solution to overcome these drawbacks. Inactivation of the sorbent when immobilized into the polymeric matrix is a key parameter to assess their performance. If the encapsulation of the sorbents is minimized, hybrid membranes are easy recovered, reactivated and functional.